HISTOPATHOLOGICAL CHANGES OF LIVER UNDER ACUTE TOXIC EFFECT OF CHLORPYRIFOS IN ALBINO RATS - Y. SAVITHRI; P RAVI SEKHAR; G. SEETHAMMA (International Journal of Pharma and Bio Sciences, 2014)
Histology, is the study of micro anatomy of specific tissues, has been successfully employed as a diagnostic tool in medical and veterinary science. The present study was aimed to examine the histopathological changes in the liver of albino rats under Transmission electron microscopy (TEM) with oral sub-lethal (20 mg/kg) administration of organo phosphate compound chlorpyrifos as single, double and multiple doses with 48 hr intervals. Structural changes were observed in liver tissues of albino rats. Chlorpyrifos-induced histopathological changes suggest that the structural integrity of certain organ systems can be disrupted to a great extent from chlorpyrifos exposure